2017
DOI: 10.1007/s11548-017-1555-z
|View full text |Cite
|
Sign up to set email alerts
|

SLIM (slit lamp image mosaicing): handling reflection artifacts

Abstract: The experiments demonstrated that integrating the proposed method to the mosaicing framework significantly improves the global photometric quality of the mosaics and outperforms existing works in SLIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The most standard approach for stitching images consists of the registration of overlapping pairs via the detection and matching of landmarks [6]. Such feature-based methods have been successfully applied for some medical applications, such as retinal mosaicking [16] and fibroscopic video mosaicking [2]. However, other type of clinical images may display a lack of texture, occlusions and other factors that make a landmarkbased registration of a pair of images not reliable enough.…”
Section: Introductionmentioning
confidence: 99%
“…The most standard approach for stitching images consists of the registration of overlapping pairs via the detection and matching of landmarks [6]. Such feature-based methods have been successfully applied for some medical applications, such as retinal mosaicking [16] and fibroscopic video mosaicking [2]. However, other type of clinical images may display a lack of texture, occlusions and other factors that make a landmarkbased registration of a pair of images not reliable enough.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive research can be found in [15]. This technique is also used in medicine such as slit lamp image mosaicing [7,16,17]. For instance, Cattin et al [16] describe an approach for mosaic retina images based on Speeded-Up Robust Features (SURF) [18].…”
Section: Image Stitchingmentioning
confidence: 99%
“…Accordingly, we include in this related work review the literature on flare spot detection. The methods found can be classified into two groups, depending on the provided input information: semi-automatic [30,27,42] and automatic [6,29].…”
Section: Related Researchmentioning
confidence: 99%
“…This fact entails a a high percentage of false positives and a low detection precision. The recent work [29] aims to detect and correct light reflections in retinal images. It detects the flare using the specular-free image concept [37] and a probability map.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation